Soil heterotrophic and autotrophic respiration respond differently to seasonal variations in temperature and water content under monsoon continental climate - Hyunjin Kim; Seungwon Kim; Sohyun Woo; Kyungjin Min (Scientific Reports)
Abstract Soil respiration (RS) comprises terrestrial ecosystems’ second-largest carbon flux. Yet, methodological errors in RS partitioning and uncertainties in seasonal responses of RS make it difficult to predict future RS. Here, we tested the assumption of RS partitioning (similar microbial respiration between planted and root-free soils), and explored two components of RS, autotrophic and heterotrophic respiration (RA, RH, respectively), in a temperate grassland under monsoon continental climate. Microbial respiration in soils from planted plots was 3.88 times higher than that from root-free plots during lab incubation. In field, RH:RS ratio was relatively low during non-monsoon, but increased during monsoon. The RH was more sensitive to temperature than RS, indicating a greater Q 10 of RH than that of estimated RA. The annual RH:RS excluding the monsoon period was comparable to those reported in the global Soil Respiration Database (SRDB) and other Korean literature. This study highlights that the assumption of RS partitioning can be violated, that RH exhibits a greater sensitivity to changes in temperature and soil water content than RA, and that annual RH:RS may be similar across the globe when extreme precipitation (e.g., monsoon) is excluded.